No one is an island: the misdirection of the individual climate impact narrative - Hutchinson, Heather; Colville, Elyse; Pratch, Grace (My University, 2023)
This paper seeks to examine, through secondary, mixed methods research, the ability of the individual to affect positive change regarding the climate crisis through their specific choices. By reading myriad scholarly, scientific, and journalistic sources, we found that though positive changes can be made on a smaller government scale, individuals’ ability to reduce environmental harm through their own choices and habits is minimal. Further, corporations and others in positions of power engage in both long- and short-term efforts to actively sabotage efforts of groups working to make societal changes or bring attention to the issues of the climate crisis. The researchers suggest that ecological communications should change direction from scolding the individual to emphasizing systemic change. It is recommended that further study be conducted of cohesion in activist organizations and collectives and the effects of education in rhetoric.
Presented on April 20, 2023 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: climate change; individualism; corporations